The constitutional principle of social market economy and its protection - Bisztyga, Andrzej; Kalus, Stanisława (KSU Publ., 2013)
The article aims at presenting the content of the constitutional principle of social market economy including the standards established by the doctrine and constitutional case law. The constituents of the principle are: freedom of economic activity, private property, and solidarity, dialogue and cooperation between social partners. The authors attempt at reconstructing the practical protection of this principle. This issue is profound as the said principle constitutes the basis of the social and economic system of the Republic of Poland.
Əлеуметтік-нарықтық экономикадағы конституциялық қағидалар жəне оның қорғанысы
Конституционные принципы в социально-рыночной экономике и его защита
Keywords: social market economy; freedom of economic activity; private ownership; solidarity; dialogue and cooperation between social partners